Model Problem Based Learning Dalam Pembelajaran Matematika SMA/SMK - Selly Rezeqi; Wardani Rahayu (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
One of the supporting components for SMA/K graduates in mathematics is curiosity, self-confidence and critical thinking skills that are formed from the experience of learning mathematics. However, students do not consider learning mathematics important because learning mathematics is considered unpleasant, so one solution these problems is to use the Problem Based Learning model. The method used is literature review by describing the results of the literature review from at least 30 relevant articles. So it can be concluded that the use of the Problem Based Learning model can improve learning skills, problem solving abilities, collaborative skills, metacognition skills, critical thinking skills, representation skills, and improve discipline.